Principal Innovation Develops P5 Students' Learning Experience Through Experiential Learning Stimulation - Heri Rifhan Halili; Khoiriyah Khoiriyah (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2024)
The purpose of this study is to show the principal's efforts to innovate the learning experience of P5 students through experiential learning. The principal's innovation develops the learning experience of P5 students with experiential learning stimulation, namely students are able to integrate Pancasila values ​​in everyday life, such as faith, noble character, and mutual cooperation, independence; strong character (unity and humanity); development of competence as active world citizens; able to solve problems in various conditions; and Demonstrate responsibility, independence and concern for issues around the environment. The learning process designed by the teachers makes students enjoy teaching and learning activities, so that learning time is really used optimally. The aspects of learning development are: 1) maximizing the classroom learning structure, 2) creating, teaching, reviewing, monitoring, and reinforcing learning expectations/rules, 3) actively involving students, 4) using a series of strategies to respond to expected student behavior, and 5) using a series of strategies to weaken unexpected student behavior.